Refugees/migrants and border security in the annual address of Poland’s foreign ministers in the years 2014–2016 - Pochyły, Piotr (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2017)
The article presents the attitudes of Poland’s foreign ministers towards refugees/migrants and border security in the years 2014–2016 expressed in their annual address. The research problem is to determine whether the ministers presented in their address generally accepted long-term strategies for all directions of foreign policy, or whether their activities in the analysed area were merely adaptive, adjusted to the current political situation in the world. The temporal scope is to determine the response after the annexation of Crimea by Russia in late February 2014 of the ministers of the Civic Platform – Polish People’s Party (PO-PSL) government in 2011–2015, and the Law and Justice (PiS) government, that came into power on 16 November 2015. The content of the address and transcripts of the proceedings of the Foreign Affairs Committee of the Polish Parliament during which the ministers discussed the theses of their speeches are the primary sources.

Od 2014 roku mieliśmy do czynienia w Europie z “gwałtownym przyspieszeniem”. Rosja zajęła Krym, wybuchł konflikt na Ukrainie. W roku następnym wystąpił kryzys uchodźczy. Cel artykuł to przedstawienie stosunku ministrów spraw zagranicznych Polski w latach 2014–2016 do uchodźców/ migrantów i bezpieczeństwa granic państwowych w dorocznych exposé. Ministrowie spraw zagranicznych Polski realizowali w analizowanym okresie generalnie adaptacyjny charakter polityki w odniesieniu do kwestii uchodźców i migrantów, a strategiczny wobec zabezpieczenia granic (wzrost znaczenia NATO, współpraca regionalna).
Kwestia uchodźców/migrantów i bezpieczeństwa granic państwowych w exposé ministrów spraw zagranicznych Polski w latach 2014–2016
Keywords: annual address; exposé; refugees; uchodźcy; foreign minister of Poland; minister spraw zagranicznych Polski; security; bezpieczeństwo; foreign policy of Poland; polska polityka zagraniczna